Synthesis of a vanadyl (IV) folate complex for the treatment of diabetes: spectroscopic, structural, and biological characterization - Naglah AM; Refat MS; Al-Omar MA; Bhat MA; AlKahtani HM; Al-Wasidi AS (Dove Medical Press, 2019)
Ahmed M Naglah,1,2 Moamen S Refat,3,4 Mohamed A Al-Omar,1 Mashooq A Bhat,5 Hamad M AlKahtani,5 Asma S Al-Wasidi6 1Department of Pharmaceutical Chemistry, Drug Exploration & Development Chair (DEDC), College of Pharmacy, King Saud University, Riyadh 11451, Saudi Arabia; 2Peptide Chemistry Department, Chemical Industries Research Division, National Research Centre, Cairo 12622, Egypt; 3Chemistry Department, Faculty of Science, Taif University, Taif 21974, Saudi Arabia; 4Department of Chemistry, Faculty of Science, Port Said University, Port Said, Egypt; 5Department of Pharmaceutical Chemistry, College of Pharmacy, King Saud University, Riyadh 11451, Saudi Arabia; 6Department of Chemistry, College of Science, Princess Nourah Bint Abdulrahman University, Riyadh 11671, Saudi Arabia Background: This study aimed to design a compound with folic acid (FAH2) and vanadyl (IV) for use in the treatment of diabetes.Materials and methods: A novel vanadyl (IV) FAH2 complex was synthesized and characterized [(FA2-)(VO2+)]·3H2O. The speculated structure of this folate complex was determined using physicochemical techniques including microanalytical analysis, conductivity studies, spectroscopic examination, magnetic measurements, thermogravimetric analyses, and morphological X-ray powder diffraction, and scanning and transmission electron microscopies. The anti-diabetic therapeutic potential of the complexes was tested in a 30-day streptozotocin-induced diabetes rat model.Results: The conductivity test of the complex implied electrolyte behavior. The spectroscopic assessments of the isolated dark yellow solid complex revealed that FAH2 acts as a bidentate ligand. The coordination process with two vanadyl (IV) ions occurred through the deprotonation of both carboxyl groups of FAH2 in a regular square pyramid arrangement at a 2(FA)2-: 2(VO)2+ molar ratio. XRD, SEM, and TEM analyses revealed the complex crystalline nature of the complex. Treating diabetic rats with vanadyl (IV) FAH2 complex significantly improved many biological parameters relevant to diabetes pathology with minimal toxicity.Conclusion: The data generated in this study indicate that the synthesized vanadyl (IV) folate complex acts as a model of anti-diabetic agent. Keywords: diabetes, vanadyl, folic acid, spectroscopic, streptozotocin, vitamin B9